1982
DOI: 10.1161/01.str.13.5.712
|View full text |Cite
|
Sign up to set email alerts
|

Fusiform basilar aneurysm as a cause of embolic stroke.

Abstract: SUMMARY Giant fusiform basilar aneurysms (dolicho-ectatic basilar anomalies) are rare and have not previously been reported to cause embolic infarction in territory distal to the aneurysm. They most commonly present as posterior fossa mass lesions with brainstem compression and cranial neuropathies. Originally considered atherosclerotic in etiology, recent authors feel that they may represent a unique arteriopathy characterized by loss of elastin in the vessel wall. We report a case which presented solely as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 24 publications
4
18
0
1
Order By: Relevance
“…Another aspect suggesting a hemodynamic mechanism is the fact that half of the patients with infarcts in the superficial PCA territory had occlusion or severe stenosis of the anterior circulation. This feature was also observed by Steel et al 8 in a patient with an occipital infarct associated with VBD and a severe stenosis of the internal carotid artery. Among infratentorial infarcts, we observed that the majority of the lesions in the arterial territories supplied by branches of the BA were contralateral to the side of the lateral displacement of the BA, which suggests a relationship between ischemia and distortion and/or stretching of the branches of the BA.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Another aspect suggesting a hemodynamic mechanism is the fact that half of the patients with infarcts in the superficial PCA territory had occlusion or severe stenosis of the anterior circulation. This feature was also observed by Steel et al 8 in a patient with an occipital infarct associated with VBD and a severe stenosis of the internal carotid artery. Among infratentorial infarcts, we observed that the majority of the lesions in the arterial territories supplied by branches of the BA were contralateral to the side of the lateral displacement of the BA, which suggests a relationship between ischemia and distortion and/or stretching of the branches of the BA.…”
Section: Discussionsupporting
confidence: 80%
“…However, in VBD other specific mechanisms, such as distortion of branches of the BA due to elongation and tortuosity of this vessel and hemodynamic factors related to the significant reduction of flow velocity in the BA, may contribute to ischemia. On the basis of the imaging and angiographic findings and exclusion of patients with other potential cause of stroke, two pathophysiological mechanisms of infarction can be identified in our series: (1) infarcts in distal territories (thalamus, superficial PCA territory, cerebellum) that may be associated with artery-to-artery embolism 8,28 and (2) brain stem and some cerebellar infarcts that may be associated with atherothrombotic occlusion at the origin of BA branches (branch atheromatous disease). 40 Our study reveals three interesting aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The elongated dilated arteries may compress and distort the brainstem and the cranial nerves and can occasionally cause obstruction of the ventricular system [2, 3, 4, 5, 6, 7, 8, 9, 10]. Brain ischemia is also known to occur and the presumptive mechanisms of stroke have been described [11, 12, 13, 14]. Flow within the dilated dolichoectatic arteries, studied by transcranial Doppler ultrasound, is often abnormal with to and fro antegrade and retrograde passage of segments of the blood column [14, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Flow within the dilated dolichoectatic arteries, studied by transcranial Doppler ultrasound, is often abnormal with to and fro antegrade and retrograde passage of segments of the blood column [14, 15, 16]. The abnormal flow patterns and regions of stagnation within the dilated arteries can cause hypoperfusion and also promote intraluminal thrombus formation [11, 12]. The orifices of penetrating and circumferential branches of the intracranial vertebral and basilar arteries can be distorted or blocked by aneurysmal deformities, atheromatous plaques and intraluminal thrombus [11, 17].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] However, pathological changes in the arterial wall, consisting primarily in defects in the internal elastic lamina with thinning of the media secondary to smooth muscle atrophy, 14 -16 may predispose patients to intracranial bleeding of various kinds. Knowledge of hemorrhagic stroke as a clinical feature of VBD has come from case reports involving a small number of patients.…”
mentioning
confidence: 99%